An Analysis of Brunei Darussalam's Plastic Furniture Market - Rio B.M.T. Hutagaol; Arief Daryanto; Hermanto Siregar (Business and Entrepreneurial Review, 2007)
This Paper Analyzes the entry mode to Brunei Darussalam Plastic furniture market and variables affecting Brunei Darussalam's demand for plastic furniture. A multiple linear regression was utilized in analyzing variables that affect the demand, using nine year data spanning from 1995 to 2003. Result of regression analysis show that price of rattan furniture, population, and the exchange rate give significant effecs on the demand. Among the recommendation, it is suggested that in the long term, Indonesia plastic furniture industry should develop its entry mode of the "wholly-owned subsidiary' in order to gain a higher profit.